Ancient Climate and Environmental History From Phytolith-Occluded Carbon - Carter, John Alec (11643832) (2007)
The best records of atmospheric change of glacial cycles are those from ice cores. However, ice cores cannot provide estimates of changes in atmospheric 13CO2 because of as of yet unresolved technical problems. One of the least understood and important influences on the changes to the isotopic composition of atmospheric CO2 are that of vascular plants. While marine benthic delta 13C records have been used to infer past changes in terrestrial vegetation, accurate estimation of changes in carbon storage on land during ice ages has proved elusive. Other estimates have been made from terrestrial biomes of pollen records but a large discrepancy between marine and land based estimates remains. This thesis offers a new method of deriving an ancient atmospheric delta 13CO2 record using measurements of phytolith-occluded carbon as a proxy. The method is designed to measure delta 13CO2 in ancient phytolith-occluded carbon and convert this signal into an atmospheric delta 13CO2 estimate for the atmosphere. Phytoliths are very small particles of silica (between 5 and 100 microns) that form distinctive and repeatable shapes in most plants. When phytoliths form within a plant, some of the host organic matter is trapped inside the phytolith. Phytoliths have been shown to contain occluded carbon and are present in most terrestrial sedimentary deposits. Moreover, because they survive well in most soils and sediments, the trapped carbon remains intact and preserved from contamination and alteration. Experiments were conducted to characterise and measure the natural variability of modern phytolith-occluded carbon. These included measurement of carbon isotopic fractionation effects between the atmosphere and whole plant material, measurement of carbon isotope fractionation between whole plant matter and phytolith-occluded carbon, and a determination of carbon compounds present in phytolith-occluded carbon. A formula was developed for separating the plant physiological factors from the atmospheric 13CO2 value in the phytolith-occluded carbon, thus providing a basis for estimating atmospheric 13CO2 values. Phytoliths were extracted and occluded carbon analysed from a 7.4m loess core. Changes in phytolith assemblages were used to create a direct record of changes to the local vegetation cover, and isotopic analyses of carbon in phytoliths to generate a record of atmospheric 13CO2 for the last 120,000 years. The record exhibits a number of periods when the atmosphere had very low delta 13CO2 values that correspond with CH4 peaks in the Vostok ice core. It is hypothesized here that these low values are a consequence of the release of large volumes of methane released from marine hydrate (clathrate) deposits into the atmosphere, thereby, diluting atmospheric 13CO2.